Characterization of Leishmania infantum species in dogs from the urban area of Cuiabá, State of Mato Grosso, Brazil - Bianca De Santis; Elizabeth Gloria Oliveira Barbosa Santos; Elisa Cupolillo; Renato Porrozzi; Amanda dos Santos Cavalcanti; Bárbara Neves dos Santos; Saulo Teixeira De Moura; Kellen Malhado; Sergio Augusto Miranda Chaves (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: Visceral leishmaniasis presents urban behavior in some Brazilian cities, with domestic dogs as the main infection source. In Cuiabá, MT, canine visceral leishmaniasis was diagnosed and characterized as recommended by the Ministry of Health. METHODS: Biological samples from suspected canine carriers were analyzed by the isoenzyme electrophoresis technique. The 6PGDH enzyme and reference strain IOC/L0566 (MHOM/BR/1975/M2903) of Leishmania (Leishmania) infantum was used as one of the controls. RESULTS: Electrophoresis analysis revealed that the canine isolates belonged to the species L. (L.) infantum. CONCLUSIONS: The authors emphasize the importance of species characterization, particularly in areas of mixed infection like Cuiabá.